1994
DOI: 10.4319/lo.1994.39.3.0520
|View full text |Cite
|
Sign up to set email alerts
|

The equatorial Pacific Ocean: Grazer-controlled phytoplankton populations in an iron-limited ecosystem1

Abstract: Experiments were conducted in the equatorial Pacific Ocean to assess the role of Fe and grazing in regulating use of N03-by the phytoplankton community. Nitrate uptake rates in situ were slow because NH,+ concentrations were inhibitory and because phytoplankton biomass was kept low by grazing. When feeding of grazers was artificially suppressed, phytoplankton net growth rate increased, biomass accumulated, and NO, -was consumed. Rapid rates of Fe uptake [40 pmol Fe (g Chl a)-' h-l] decreased by an order of mag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

19
219
6
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 307 publications
(245 citation statements)
references
References 25 publications
(25 reference statements)
19
219
6
1
Order By: Relevance
“…This hypothesis, in its broadest form, states that the cell division rates of the small phytoplankton that dominate the indigenous community are relatively fast and are ''not strongly'' limited by iron (not to the extent that is Ͻ1/2 max ; Cullen 1995). These cells are dependent on recycled nutrients (Price et al 1994;Landry et al 1997), and any increases in number following iron addition are rapidly cropped by quickly growing microzooplankton grazers (Banse 1982;Landry et al 1997). In contrast, large cells with relatively small surface area to volume ratios are at a competitive disadvantage for NH and Fe assimilation be-ϩ 4 cause of diffusion limitation (Morel et al 1991a) and are iron limited.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…This hypothesis, in its broadest form, states that the cell division rates of the small phytoplankton that dominate the indigenous community are relatively fast and are ''not strongly'' limited by iron (not to the extent that is Ͻ1/2 max ; Cullen 1995). These cells are dependent on recycled nutrients (Price et al 1994;Landry et al 1997), and any increases in number following iron addition are rapidly cropped by quickly growing microzooplankton grazers (Banse 1982;Landry et al 1997). In contrast, large cells with relatively small surface area to volume ratios are at a competitive disadvantage for NH and Fe assimilation be-ϩ 4 cause of diffusion limitation (Morel et al 1991a) and are iron limited.…”
mentioning
confidence: 99%
“…The iron hypothesis explains these observations by maintaining that phytoplankton productivity and biomass are limited by iron (Martin et al 1991;Coale et al 1996b). Indeed, ambient iron levels are low in high-nutrient low-chlorophyll (HNLC) areas (Martin et al 1991;Coale et al 1996b), and the addition of iron to incubation bottles has been shown to increase net growth rates, chlorophyll yields, nitrate uptake, and nutrient consumption, particularly of the larger cells Martin et al 1991;Price et al 1991Price et al , 1994Takeda and Obata 1995;Fitzwater et al 1996). The ecumenical hypothesis (Morel et al 1991b;Price et al 1994;Cullen 1995) and the recent synthesis of data from the equatorial Pacific by Landry et al (1997) extend this explanation by invoking both iron limitation and grazing to explain the HNLC regions.…”
mentioning
confidence: 99%
See 3 more Smart Citations